An Efficient, Optimized Synthesis of Fentanyl and Related Analogs - Valdez, Carlos A.; Leif, Roald N.; Mayer, Brian P. (PLOS ONE, 2014)
The alternate and optimized syntheses of the parent opioid fentanyl and its analogs are described. The routes presented exhibit high-yielding transformations leading to these powerful analgesics after optimization studies were carried out for each synthetic step. The general three-step strategy produced a panel of four fentanyls in excellent yields (73–78%) along with their more commonly encountered hydrochloride and citric acid salts. The following strategy offers the opportunity for the gram-scale, efficient production of this interesting class of opioid alkaloids.